UPAYA MENINGKATKAN PENERIMAAN PAJAK DAERAH OLEH DINAS PENGELOLAAN KEUANGAN DAN ASET KABUPATEN ROKAN HULU - -, Erlina (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
This research has been done in theDinas pengelolaan Keuangan dan AsetKabupaten Rokan Hulu, The purpose is totknow the efforts that has been done DinasKeuangan dan Aset Kabupaten Rokan Huluto increase income District tax.The informants of data are leaderDinas and Aset, Leader of area PendapatanAsli Daerah dan three leaders Seksi BidangPendapatan Asli Daerah. This research isqualitative research, where is we get the datafrom the explanation of arranged thesentences as systematic and than we get theconclusion of the research.The efforts to increase income Districttax:1. Increasing the quality SDM of employerpengelolaan pajak daerah througheducation and training.2. Make Intensification district tax by findout the source District tax that not yetfind by the worker district tax.3. Make intensification district tax troughincreasing the total of obliged tax.4. Doing coordination with another official,data collection, the effectively pressing aclaim, supervision, act.5. Increase tool and infrastructure.In this research the writer gives thesuggestions:1. For leader structural DPKA in order thatmake illumination about district tax2. For all workers hoped work well anddiscipline and give explanation aboutdistrict tax for the society.